Application of low-frequency eddy current testing to the inspection of a double-walled tank in a reprocessing plant. Issue 2 (3rd April 2018) - Tajima, Naoki; Yusa, Noritaka; Hashizume, Hidetoshi
Abstract: This paper discusses the applicability of simple low-frequency eddy current testing to the detection of deeply embedded flaws. The study specifically considered a double tank in a reprocessing plant for extracting plutonium-uranium from spent nuclear fuels. The tank was modelled by two type 304 austenitic stainless steel plates situated with an air gap of 80 mm, and the change in the thickness of one of the plates was detected through the other plate and the air gap. Axisymmetric two-dimensional finite element simulations were conducted and found that a simple circular coil with a large diameter enabled to detect the thickness based on the magnetic flux density at the centre of the coil although the plates were as thick as 30 mm. The results of the numerical simulations were validated by experiments.